Puerto Nuevo the landscape rehabilitation of the Philippine South Harbor Port Area into a mixed-use marina development - Casimiro, Fatima Maria G. (Quezon City College of Architecture, University of the Philippines Diliman, 2014)
The Philippines is an archipelagic country and maritime transport plays a vital role in regional socioeconomic development. The Port of Manila is an example of an important node as an entry point into the capital of the Philippines. It has served as a trading, transportation and even tourism site even before the Spaniards came to our country. The South Harbor Port Area caters to multifarious activities and services like barging/ lighterage operations, cargo handling services, milling, manufacturing and distribution/ consolidation activities, passenger ferry services, ship repair and dockyard, food catering services, cargo handling contractors and lessees, and commodity handling (Profile of Ports, 2000).
Recently, the government has issued commission for the rehabilitation of the whole South Harbor Port which will encompass the areas of the main port has its adjacent bodies of waters, the extension port and the arrival areas. The Philippine South Harbor Port Area is now faced with serious environmental problems, such as water pollution in its surrounding bodies of water (i.e Manila Bay and Pasig River), flooding, coastal erosion and waterfront deterioration, massive air pollution, biological extinction and high production of waste. The restoration of the imageability of South Harbor can help alleviate problems in the deterioration of the landscape.
At present, port and navigational facilities on site are not fit for the majority of users wherein the site projects a general characteristic of ruins and run downed areas, It is inevitable that significant changes in landscape design shall be integrated in order to uplift the standards of the import and export industry, maritime community, naval operations and the tourism sector of the Philippines. The study will directly affect the citizens of Manila in terms of economic and urban development.
Best Thesis (Landscape Architecture) AY 2013-2014, 3rd place
Thesis (Bachelor of Landscape Architecture)--University of the Philippines Diliman
Keywords: Philippine South Harbor Port Area -- Rehabilitation .; South Harbor (Port Area, Manila)